Finite time fractional order ISMC with time delay estimation for re-entry phase of RLV with enhanced chattering suppression. (January 2023) - Sarkar, Rajasree; Amrr, Syed Muhammad; Bhutto, Javed Khan; Saidi, Abdelaziz Salah; Algethami, Abdullah; Banerjee, Arunava
Abstract: This paper investigates the attitude controller design for the reusable launch vehicle (RLV) in its re-entry phase under the influence of model uncertainties and external disturbances. The navigation of RLV along a predefined safe trajectory is a challenging task since the RLV system dynamics has a complex nonlinear behaviour with uncertain environmental conditions. Therefore, this paper proposes a time-delay estimation technique with fractional order integral sliding mode control abbreviated as FOISMC-TDC, for efficient tracking of a pre-designed reference trajectory that ensures safe landing of the RLV. The time delay estimation method in the proposed research employs the input–output information of the immediate past instant to estimate any uncertainties and un-modelled dynamics. The estimated value is then fed to the composite control for disturbance compensation without primarily relying on the switching control of FOISMC approach. This in turn, eliminates the problem of high-frequency chattering in the control input. In addition, by using FOISMC philosophy finite time convergence of system states is achieved with desired error response. Furthermore, Lyapunov and homogeneity theories have been utilized to establish practical finite-time stability of the overall closed loop system. Numerical analysis with state-of-the-art techniques have also been presented to demonstrate effectiveness of the proposed methodology. Highlights: Fractional order ISMC with time-delay estimation technique for RLV system. Lyapunov and homogeneity theories ensure practical finite-time stability. Achieve chattering suppression & exemption from knowing the upper limit of disturbance. Simulation demonstrates efficient tracking as compared to state-of-the-art methods.